2023
DOI: 10.1002/cam4.5897
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in survival and care across social determinants of health in a cohort of advanced lung cancer patients in Quebec (Canada): A high‐resolution population‐level analysis

Abstract: Background: Advanced lung cancer patients exposed to breakthrough therapies like EGFR tyrosine kinase inhibitors (EGFR-TKI) may experience social inequalities in survival, partly from differences in care. This study examined survival by neighborhood-level socioeconomic and sociodemographic status, and geographical location of advanced lung cancer patients who received gefitinib, an EGFR-TKI, as first-line palliative treatment. Differences in the use and delay of EGFR-TKI treatment were also examined. Methods:L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A population-based retrospective study in Quebec investigated survival inequities in advanced lung cancer patients by income, education, material deprivation index, immigration, and geographic region, as well as variations in the use and delay of targeted therapy ( EGFR -TKI treatment). Patients residing in areas with low education, high material deprivation, minimal immigrant density, or in rural areas or urban centers other than Montreal, had shorter median survival times than patients from Montreal [ 19 ]. Data from the United Kingdom suggest that as the index of multiple deprivation (a measure of the general poverty of a geographic area) increases, the likelihood of patients receiving any novel anticancer therapy, any targeted therapy, or immunotherapy decreases [ 20 ].…”
Section: Why Is Timely Access To Molecular Testing Results An Imperat...mentioning
confidence: 99%
“…A population-based retrospective study in Quebec investigated survival inequities in advanced lung cancer patients by income, education, material deprivation index, immigration, and geographic region, as well as variations in the use and delay of targeted therapy ( EGFR -TKI treatment). Patients residing in areas with low education, high material deprivation, minimal immigrant density, or in rural areas or urban centers other than Montreal, had shorter median survival times than patients from Montreal [ 19 ]. Data from the United Kingdom suggest that as the index of multiple deprivation (a measure of the general poverty of a geographic area) increases, the likelihood of patients receiving any novel anticancer therapy, any targeted therapy, or immunotherapy decreases [ 20 ].…”
Section: Why Is Timely Access To Molecular Testing Results An Imperat...mentioning
confidence: 99%
“…For example, one study found that the percentage of individuals with survival <1 year after diagnosis in Black individuals and White individuals was 41.4% and 22.2% for lung cancer, 9.8% and 7.1% for colorectal cancer, and 2.9% and 0.7% for breast cancer, respectively (Cui and Finkelstein, 2022). Another study showed that patients with advanced lung cancer living in the most materially deprived areas had the shortest median survival time (Qureshi et al, 2023). Hamers et al (2020) found that, out of all patients diagnosed with stage IV colorectal cancer between 2008 and 2016 in the Netherlands Cancer Registry, OS improved only for those patients who were already doing well compared with others.…”
Section: Introductionmentioning
confidence: 99%
“… 2 With the development of medical technology, the terminal stage of advanced cancer patient life may be prolonged, but it has not significantly succeeded in improving the cure rate of cancer. 3 With the development of medical technology, the life of patients with advanced cancer is prolonged, but the physical function of patients is declining, the quality of life is decreasing, and the degree of dependence on the lives of caregivers is becoming stronger. At the same time, patient privacy is not protected, due to the lack of independent mobility, patients need to be cared for all the time, lack privacy space and time.…”
Section: Introductionmentioning
confidence: 99%
“…(2) refuse examination, diagnosis, and treatment of the primary disease. (3) The concept of receiving hospice care has the demand and willingness of hospice care. This study summarized the hospice care needs of patients with advanced cancer and the current situation of hospice care, and analyzed the influencing factors of hospice care needs in order to provide a reference for better clinical practice of hospice care.…”
Section: Introductionmentioning
confidence: 99%